2006
DOI: 10.1590/s1413-86702006000500009
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of adherence on abiotic and cellular surfaces of Acinetobacter baumannii strains isolated from catheter tips

Abstract: The cell surface hydrophobicity and adhesion to abiotic and cellular surfaces was tested in five clinical strains of Acinetobacter baumannii isolated from catheter tips. Biochemical and molecular characteristics of these strains were also studied. Hydrophobicity was characterized by a test for affinity to xylene. Adhesion to abiotic surfaces (polystyrene, formica, latex and glass) was evaluated in Petri plates using the stamp technique. Buccal epithelial cells were used for tests of adhesion to cellular surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Accordingly, the hydrophobicity of the isolates was evaluated by determining the affinity of cells to hexadecane (Rosenberg, 1984). The results obtained from the MATH method revealed that the majority of A. baumannii strains isolated from a hydrophobic medical device surface showed a hydrophilic character which contradicts several studies which admitted that the hydrophobic cells tend to adhere to a hydrophobic substrate, while the hydrophilic cells tend to adhere to a hydrophilic substrate (Costa et al, 2006;Djeribi et al, 2013). It is suggested that there is a positive correlation between the degree of bacterial hydrophobicity and the adhesion to abiotic surfaces (Costa et al, 2006;Pour et al, 2011).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Accordingly, the hydrophobicity of the isolates was evaluated by determining the affinity of cells to hexadecane (Rosenberg, 1984). The results obtained from the MATH method revealed that the majority of A. baumannii strains isolated from a hydrophobic medical device surface showed a hydrophilic character which contradicts several studies which admitted that the hydrophobic cells tend to adhere to a hydrophobic substrate, while the hydrophilic cells tend to adhere to a hydrophilic substrate (Costa et al, 2006;Djeribi et al, 2013). It is suggested that there is a positive correlation between the degree of bacterial hydrophobicity and the adhesion to abiotic surfaces (Costa et al, 2006;Pour et al, 2011).…”
Section: Discussionmentioning
confidence: 69%
“…Cell surface hydrophobicity (CSH) of A. baumannii strains is also known to be associated with pathogenicity, bacterial adhesion and biofilm formation (Costa et al, 2006;Pour et al, 2011). Accordingly, the hydrophobicity of the isolates was evaluated by determining the affinity of cells to hexadecane (Rosenberg, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been demonstrated to exhibit cell surface hydrophobicity, an important determinant bacterial adhesion. For a successful infection to occur, bacteria must successfully adhere to host cells (24). The hydrophobicity of a microorganism protects it from being phagocytosed and appears to play an important role in its attachment to various polymers.…”
Section: Pathogenesis Virulence Factors and Resistancementioning
confidence: 99%
“…For example, the urease activity of Acinetobacter promotes colonization of the mouse stomach (24). Urease also helps Acinetobacter spp.…”
Section: Pathogenesis Virulence Factors and Resistancementioning
confidence: 99%